STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN PENJUALAN PADA BATIK NURHIKMAH DI KELURAHAN JELMU KOTA JAMBI - Rahmadani; Muhamad Subhan; Eri Nofriza (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze sharia marketing strategies in increasing sales of Nurhikmah batik and analyze the advantages and disadvantages of sharia marketing strategies in Nurhikmah batik in Jelmu sub-district, Jambi city. The main objective of this study is to determine and analyze sharia marketing practices and the implementation of sharia marketing principles in Nurhikmah batik. This study is a qualitative study with the type of research used, namely data collection methods using interviews, observation and documentation, data validity checking techniques using triangulation techniques, and data analysis techniques. The results of this study indicate that an important sharia marketing strategy using 4P to increase sales. One of the main solutions that can be optimized is the use of social media as a broad and dynamic marketing platform. Social media is a very potential tool to expand market reach and increase consumer awareness of the Nurhikmah batik brand. By utilizing popular platforms such as Instagram, Facebook, and TikTok, Rumah Batik Nurhikmah can reach a wider audience.